Hubungan Dukungan Keluarga Dengan Kualitas Hidup Lansia - Valentina Br Tambunan; Edi Purwanto (Poltekkes Kemenkes Kalimantan Timur, 2024)
Healthy older adults are those who are able to care for themselves independently without the help of others in terms of disease prevention, functional capacity, recovery, and rehabilitation, which are owned by the elderly themselves. The design used in this study was descriptive correlational with a cross-sectional approach. The population was taken from all elderly patients in the working area of the Lambing Health Center, 73 people. The sample technique used was purposive sampling. The research instruments used were questionnaires on respondent characteristics, WHOQOL-BREF, and family support. Statistical analysis was performed with the chi-square test. The results presented in this study showed that the category of good family support (70.0%), the category of good quality of life for the elderly (60.3%), and the chi-square test for the relationship between family support and quality of life for the elderly yielded small values above ρ value = 0.00 and smaller than the value of α = 0.05. There is a significant relationship between family support and quality of life of the elderly in the work area of the Lambing Health Center. Keywords: family support, quality of life, elderly.